OBSERVATIONAL RESULTS OF CALIBRATION AND NAVIGATION COSMIC APPARATUS (CA) - Shumilov, Yu. P.; Dobrovolsky, A. V.; Paltsev, N. G.; Medvedev, Yu. A.; Petrov, M. P.; Chaichuk, R. A.; Korniychuk, L. V.; Tomak, L. F.; Depenchuk, E. A. (Одеські астрономічні публікації, 2017)
Results are represented of photometric observation of nine calibration and navigation cosmic apparatus obtained at the Odessa Astronomical Observatory in September-October 1995.